Aircraft Noise: Annoyance, House Prices and Valuation - Brooker, Peter (Institute of Acoustics, 2006)
“Nobody wants to buy your house. It’s the aircraft noise. You’ll have to reduce the price a lot.” Aircraft noise around airports causes annoyance, and tends to reduce the price of affected properties. Can annoyance be ‘costed’ by examining house price reductions? Are there other ways of valuing annoyance in monetary terms? This short paper summarises key research results and poses some questions.